Coating-free, air-stable silver nanowires for high-performance transparent conductive film. (5th July 2018) - Tang, Long; Zhang, Jiajia; Dong, Lei; Pan, Yunmei; Yang, Chongyang; Li, Mengxiong; Ruan, Yingbo; Ma, Jianhua; Lu, Hongbin
Abstract: Silver nanowire (Ag NW) based films are considered as a promising alternative for traditional indium tin oxide but still suffer from some limitations, including insufficient conductivity, transparency and environmental instability. We here report a novel etching synthesis strategy to improve the performance of Ag NW films. Different from the traditional methods to synthesize high aspect ratios of NWs or employ electrically conductive coatings, we find it effective to reduce the high-reactivity defects of NWs for optimizing the comprehensive performance of Ag NW films. In this strategy etching can suppress the generation of high-reactivity defects and meanwhile the etching growth of NWs can be accomplished in an uneven ligand distribution environment. The resulting Ag NWs are uniformly straight with a sharp-edged structure. The transparent conductive film obtained exhibits simultaneous improvements in electrical conductivity, transparency and air stability. Even after exposure in air for 200 days and no protective coatings, the film can still meet the highest requirement of practical applications, with a figure of merit 361 (i.e., FoM > 350). These results not only demonstrate the importance of defect control in the synthesis of Ag NWs, but also pave a way for further optimizing the performance of Ag NW-based films.